Поликлоновая структура европейских серебряных карасей Carassius auratus s. lato в водоемах Украины - Межжерин, С.В.; Кокодий, С.В. (Видавничий дім "Академперіодика" НАН України, 2008)
As a result of the biochemical gene marking and the cytometric and morphometric analyses, the proof of the presence and the description of 5 clonal forms of unisex silver crucian carp C. gibelio and their hybrids with bisexual goldfish C. auratus in reservoirs of Ukraine are given. Most likely, clonal forms have taken place at the hybridization of not less than four initial parental species. We have emphasized the biological heterogeneity of forms C. gibelio which consists: in the presence or absence of males; opportunities of hermaphroditism; hybridizations with C. аuratus. The key morphological attributes are given, allowing to distinguish clonal forms C. gibelio on series, and the problems of systematization with reference to polyclonal kinds are discussed.